Outbreak of Piv-3 in a Neonatal Intensive Care Unit in England. Issue 3 (March 2017) - Dunn, Gemma Louise; Tapson, Helen; Davis, Jonathan; Gobin, Maya
Abstract : An outbreak of PIV-3 in a neonatal ICU was investigated using a retrospective cohort study. Risk of infection increased with lower birth weight and gestational age. Contact with sick visitor(s)/staff was not associated with infection ( P = 0.212, P = 0.299). Transmission routes are difficult to identify, and the importance of visiting restrictions and sickness absence during outbreaks is recommended.